Culture of innovation through customer experience practices (Research, Society and Development, 2021)
The aim of this study is to analyze and identify how the Customer Experience practices, together with the Culture of Innovation, can bring results to companies. The actions to monitor and improve the customer experience lead the company to redesign customer interactions at all points and moments of contact. Mapping your customers' journeys and the most important contact points leads to the implementation of an innovative organizational culture that will govern all the company's internal and external relations actions. The research methodology used was an exploratory research, based on the application of questionnaires built with theoretical apparatus based on good practices applied in large companies, on Culture of Innovation, Customer Success and Customer Experience, an interface between these three fields through a comparative analysis , via a questionnaire, with 24 companies participating in the Local Innovation Agent Project (ALI) from various micro and small segments, located in the northern region of the city of São Paulo, selected by Sebrae. As a result, it is expected to be able to contribute to the improvement of the management of companies that participate in the ALI Project and, mainly, in their entrepreneurial behavior.